Warpage of injection mouldings in hybrid moulds with epoxy-aluminium composite core - Silva, M. A. (2010)
Hybrid moulds with mouldings blocks made with epoxy composites are being used in injection mouldings of precision parts. The epoxy composites are vacuum cast in silicone moulds. The cycle time is substantially increased by the low thermal conductivity of these epoxy composites. Consequently the structure and the shrinkage of the mouldings are very different from mouldings in conventional moulds. In this study amorphous (polystyrene) and semi-crystalline (polypropylene) materials were injection moulded in a 3D complex moulding. A hybrid mould with moulding core in an epoxy composite with 60% of aluminium powder and moulding cavity in steel was used. The warpage of the mouldings details resulting from the changing materials and the processing conditions was analysed. The software Moldex3D was used to predict the shrinkage and the warpage.